Alternatives of how to prepare for the future labor market - Szőcs, Andor; Hamvas, László (METSZETEK Társadalomtudományi Folyóirat, 2022)
What happens if among the members of a society and among the smaller and larger units and groups making up the society trust and confidence seems to be disappearing at once? What happens if confidence reposed into each other fall victim to social differences as well as to the economic / cost-of-living boxing of modern information society? How to stop the crisis symptom that seems to be developing this way and which is shown in the fragmentation of communities?1 With other words, is it possible to “stick again together” a community or even a whole society started to disintegrate? The questions, even if not so characteristically phrased, provide sociologists actually with the scope of understanding our modern, individualistic world (Habermas 1994). Gusfield (1975) depicts dichotomy of community and society in a way that we should interpret community as a pervading, significant contrast. By now literature seems as if it was only be able to picture the changes taking place in the images both of the society and community describing them by even more pronounced, contradictory processes. The changes that send messages on the disintegration of categories and frames becoming insecure instead of the security and integration quasi missed by Habermas. It also seems as if—quasi as an answer given to this process—occlusion/seclusion both on the part of community members and the various communities from the seemingly unknown and insecure changes were more intensive (Légmán 2012). We intend to construe these phenomena on the next pages, but due to extension limits without the need for completeness of social interpretations. We want to do it with the help of mainly one dimension: value preference through the example of a given society, namely the Hungarian one. Thus we get to the stability and the solidarity of the members of the smallest unit of society, one which accepts and expresses various value preferences, the family. From time immemorial, one of the crucial questions of mankind has been what the future has in store for us. The future, however, has remained unfathomable up to this day, and even future studies promises only as much as prognosticating what is likely to continue and what will plausibly change in the world. Thus, no wonder, that already the first “real” economists of the 18th century (Adam Smith et al.) considered the creation of the future model of labor economy as a challenge. At the present era of modern labor market, this task is closely connected with the future status of labor market since in a consumer society income acquired by work forms the basis of satisfying needs (Ehrenberg – Smith 2003, Galasi 1994). We are not saying anything new by stating the fact that the demand for labor force is determined by new places of work and that an ideal supply of labor force must be adaptable to the requirements of demand. To meet requirements and to be adaptable is possible only if we are armed with the necessary competencies and capital (Hodges – Burchell 2003, Bourdieu 1998). The question, to what extent students in higher education are prepared for changes in the demand for labor force, arises at this point. What can young people expect on the labor market in this ever changing world? What kind of job opportunities and work conditions are there for them, and how much are they prepared to face these changes?